HIV and Human Coronavirus Coinfections: A Historical Perspective - Palesa Makoti; Burtram C. Fielding (Viruses, 2020)
Seven human coronaviruses (hCoVs) are known to infect humans. The most recent one, SARS-CoV-2, was isolated and identified in January 2020 from a patient presenting with severe respiratory illness in Wuhan, China. Even though viral coinfections have the potential to influence the resultant disease pattern in the host, very few studies have looked at the disease outcomes in patients infected with both HIV and hCoVs. Groups are now reporting that even though HIV-positive patients can be infected with hCoVs, the likelihood of developing severe CoV-related diseases in these patients is often similar to what is seen in the general population. This review aimed to summarize the current knowledge of coinfections reported for HIV and hCoVs. Moreover, based on the available data, this review aimed to theorize why HIV-positive patients do not frequently develop severe CoV-related diseases.